Implementation of History Textbooks as A Learning Resource at SMA Brigjend Katamso 1 Medan - Nadiyah Zahra Lubis; Benny Junior Kaban; Surya Aymanda Nababan; Muhammad Adika Nugraha; Dedi Kusbiantoro; Muhammad Ricky Hardiyansyah; Fikri Alkhairi (Keguruan, 2023)
History textbooks play an important role in the history learning process at SMA Brigjend Katamso 1 Medan. These textbooks become the main source of information and understanding of historical events for students. The implementation of history textbooks shows a systematic and structured effort in incorporating historical material into the school curriculum. The use of high-quality history textbooks provides accurate and in-depth information about historical events, helping students understand their context. While important, the use of history textbooks also faces challenges such as limited information, the need to update content according to the latest research, and maintaining an inclusive diversity of historical perspectives. The use of history textbooks can improve history learning at SMA Brigjend Katamso 1 Medan by helping students gain a better understanding of history and relate it to the current social, political, and cultural context. This research is a library research where research is based on previous literature searches that are relevant to the problems discussed in this study. The data collected in this study were obtained through excavation and tracing of books, articles, magazines, journals, internet access, and other important records related to the subject of this study and can help understand the issues discussed. However, this research is descriptive analytical, which means collecting data, interpreting it, then analyzing and interpreting it.